Pengaruh Lingkungan Kerja Fisik dan Pengembangan Karir Terhadap Disiplin Kerja Pegawai - Windi Permadi Rahmat; Arga Sutrisna; Mila Karmila (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
The purpose of this study was to determine the effect of physical work environment on employee work discipline at Perusahaan Daerah Air Minum (PDAM) Tirta Sukapura Kab. Tasikmalaya, to determine the effect of career development on employee work discipline at Perusahaan Daerah Air Minum (PDAM) Tirta Sukapura Kab. Tasikmalaya and to determine the effect of physical work environment and career development on employee work discipline at Perusahaan Daerah Air Minum (PDAM) Tirta Sukapura Kab. Tasikmalaya. The sample in this research is employees Perusahaan Daerah Air Minum (PDAM) Tirta Sukapura Kab. Tasikmalaya in all sections, totaling 77 people. This research was conducted by collecting data using a questionnaire, and testing the data used was multiple linear regression analysis. Based on the research results, it can be seen that: (1) The application of physical work environment and career development is very good and encourages the level of employee discipline; (2) Physical Work Environment and Career Development simultaneously have a significant effect on Employee Work Discipline; (3) Physical Work Environment partially does not affect Employee Work Discipline; (4) Career Development partially has a significant effect on Employee Work Discipline.